2014
DOI: 10.1155/2014/141378
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Biogenic Particles in the Snow of the Cities of the Russian Far East as Potential Allergic Compounds

Abstract: This paper presents an analysis of airborne biogenic particles (1 mkm–1 mm) found in the snow in several cities of the Russian Far East during 2010–2013. The most common was vegetational terraneous detritus (fragments of tree and grass leaves) followed by animal hair, small insects and their fragments, microorganisms of aeroplankton, and equivocal biological garbage. Specific components were found in samples from locations close to bodies of water such as fragments of algae and mollusc shells and, marine inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…On average, even carbon numbered α-, β-and ω-hydroxy FAs in their total mass concentrations account for ∼ 69, 68 and 84 %, respectively. The even carbon number predominance is also found in recent marine and lacustrine sediments (Cardoso and Eglinton, 1983;Goossens et al, 1986;Kawamura, 1995;Zhang et al, 2014). Similar to our study, Volkman et al (1980) documented the bimodal distribution of α-hydroxy FAs with peaks at C 16 and C 24 in the intertidal sediments from Victoria, Australia, and attributed their contribution from sea grass (i.e., Zostera muelleri) detritus owing to similar distribution patterns.…”
Section: Concentrations Of Hydroxy Fatty Acidssupporting
confidence: 86%
See 1 more Smart Citation
“…On average, even carbon numbered α-, β-and ω-hydroxy FAs in their total mass concentrations account for ∼ 69, 68 and 84 %, respectively. The even carbon number predominance is also found in recent marine and lacustrine sediments (Cardoso and Eglinton, 1983;Goossens et al, 1986;Kawamura, 1995;Zhang et al, 2014). Similar to our study, Volkman et al (1980) documented the bimodal distribution of α-hydroxy FAs with peaks at C 16 and C 24 in the intertidal sediments from Victoria, Australia, and attributed their contribution from sea grass (i.e., Zostera muelleri) detritus owing to similar distribution patterns.…”
Section: Concentrations Of Hydroxy Fatty Acidssupporting
confidence: 86%
“…Lipid biomarkers from terrigenous plants, algae, fungi and soil microorganisms have been reported extensively in aerosols (Conte and Weber, 2002;Gagosian et al, 1987Gagosian et al, , 1981Kawamura, 1995;Kawamura et al, 2003;Simoneit, 1977;Simoneit et al, 2004), sediments (Kawamura, 1995;Kawamura and Ishiwatari, 1984;Kawamura et al, 1987;Zhang et al, 2014), ice cores (Sankelo et al, 2013) and rain/snow (Kawamura and Kaplan, 1986;Satsumabayashi et al, 2001;Yamamoto et al, 2011). These studies have utilized fatty acids as a proxy to assess the terrigenous contribution of higher plant waxes to various environmental samples owing to their abundant presence in biopolymers of plants and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to LPS mass, estimated concentrations of GNB dry cell mass are higher than those obtained in our earlier study conducted for fresh snow samples from Sapporo (average 26.3 µg kg −1 in 2010 and 19.3 µg kg −1 in 2011) [ Tyagi et al ., ]. Golokhvast [] reported that airborne biogenic particles, which could be scavenged by snow, can cause allergies to pedestrians in the Russian Far East. Additionally, Lee et al .…”
Section: Resultsmentioning
confidence: 99%
“…Still, whatever the exact cause, it is unexpected given the remoteness of the location and poses the question “Where does it all come from?” It is conceivable that airborne MPs are emitted or dispersed locally by ships and by wind. Snow from the Vladivostok district contained particles of marine origin, including sea urchins, algae, and mollusk shells ( 30 ). Still, most of the particles likely originate from more distant regions.…”
Section: Discussionmentioning
confidence: 99%